(untitled) (Revista de Estudos em Municipalidade, 2026)
The Single Registry was established in 2001 with the purpose of unifying the registry of beneficiaries of social programs in force at the time, in order to make public management more practical. The article analyzed the applicability of the Single Registry in social assistance policy in the municipalities of the micro-regions of Nanuque and Teófilo Otoni, located in Vale do Mucuri, in the state of Minas Gerais, from 2019 to 2021. To this end, data research was carried out of the municipalities that make up Vale do Mucuri/MG in 2020, listed on the Vis Data 3 Beta portal of the Secretariat for Evaluation and Information Management (SAGI) linked to the Ministry of Citizenship. It was found that this is an instrument with the potential for identifying and socioeconomic characterization of families in situations of social vulnerability. The results revealed that the municipalities of Santa Helena de Minas, Bertópolis and Fronteira dos Vales belonging to the microregion of Nanuque-MG presented a Single Registry per capita indicator above 55% of people registered in extreme poverty. In the microregion of Teófilo Otoni/MG, the municipalities of Ouro Verde de Minas, Catuji and Setubinha had a percentage of extremely poor registered people above 57% in relation to the registered population.